Supraventricular arrhythmia following patent foramen ovale percutaneous closure. (3rd October 2022) - Guedeney, P; Laredo, M; Zeitouni, M; Hauguel-Moreau, M; Wallet, T; Alamowitch, S; Sabben, C; Deltour, S; Benyounes, N; Obadia, M; Collet, J P; Rouanet, S; et al.
Abstract: Background: Randomized studies have reported low rates of atrial fibrillation (AF) after patent foramen ovale (PFO) closure (<6%) but have relied on patients-reported symptomatic episodes, thus true incidence and timing of AF after PFO closure remain unknown. Objective: To prospectively determine the incidence, timing, and determinants of supraventricular arrhythmia following PFO closure based on loop recorder monitoring. Methods: Cardiac monitoring was proposed to all patients after PFO closure from June 2018 to October 2021 in our center by mean of implantable loop recorder (ILR) monitoring in patients considered at higher risk of AF (age ≥55 years, associated cardiovascular risk factors, prior palpitations, or documented supraventricular ectopic activity) or 4-week external loop recorder (ELR) monitoring in other patients. The primary endpoint was the incidence of AF, flutter, or atrial tachycardia lasting >30 seconds within 28 days of the procedure. Determinants of the primary endpoint were assessed with stepwise logistic regression model. Results: A total of 225 patients were included. The primary endpoint occurred in 47/225 (20.9%) patients, including n=13 (9.9%) and n=24 (28.9%) among ELR- and ILR-monitored patients, respectively. Among ILR-monitored patients, median follow-up was 428 (211–752) days, and four more cases of supraventricular arrhythmia were diagnosed beyond 28 days (Figure 1). Overall, median delay from procedure to arrhythmia was 14.0 (6.5–19.0) days and half of these patients reported symptomatic episodes. Determinants of the primary endpoint were older age (adjusted odds ratio [aOR]: 1.67, 95% confidence interval [CI]: 1.18–2.36, per 10-year increase), device left disc diameter ≥25mm (aOR: 2.67, 95% CI: 1.19–5.98) and male sex (aOR: 4.78, 95% CI: 1.96–11.66) (Figure 2). Conclusion: Using prolonged loop recorder monitoring, supraventricular arrhythmia was diagnosed in one patient out of five with a median delay of 14 days suggesting that this post-procedural event has been so far, underestimated. Funding Acknowledgement: Type of funding sources: None.